Daud and Mephibosheth: Reconstruction of the meaning of Inheritance Rights Justice for Persons with Disabilities in 2 Samuel 9:1-13 - Laurentius Khoswandy, Geovanny Geraldy (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2024)
The condition of a person's disability is still a hot polemic to be discussed. One of the problems that is often overlooked or even normalized by today's people is the granting of inheritance rights for people with disabilities. Their situation as persons with disabilities keeps them from getting their full rights in the inheritance that they should get. Persons with disabilities are considered unable to obtain or even unable to manage these rights/inheritance. This of course creates a new oppression for them as persons with disabilities because they cannot receive what they should get. Inheritance problems for people with disabilities can actually be found in the Bible. One of the Bible stories that today's Christians may rarely know is about one of the children of Jonathan, David's friend, Mephibosheth. Jonathan's son is a person with a disability because his legs are lame as a result of an incident in his childhood. Mephibosheth's condition as a person with a disability meant that he was denied his rights as the grandson of King Saul (a descendant of the royal family). Therefore, through this paper, using a simple historical critical method, I want to show and dismantle the problem of injustice for persons with disabilities, especially in terms of inheritance. In addition, considering that this paper uses a disability perspective, of course it will at least provide a new perspective on the issue of inheritance rights for persons with disabilities by prioritizing aspects of justice and equality which so far have been underestimated.